Towards a city-based cultural ecosystem service innovation framework as improved public-private-partnership model: A case study of kaohsiung dome - Min-Ren Yan; Hui-Lan Chi; Jui-Ying Yang; Kuo-Ming Chien (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
This paper explains the concept of a city-based cultural ecosystem service, and how innovations and systematic operations management can help an international city to improve the efficiency and effectiveness of the Public-Private Partnership (PPP) model. Previous studies suggest that most of the PPP models focus on the operation and analysis of PPP construction projects, limited attention of the subsequent operations and management for PPP facilities. This paper thus proposed an integrated PPP management framework with the principles of Cultural Ecosystem Service (CES) and open innovation to support better operations management of PPP projects. While the management of modern PPP projects will inevitably encounter the challenges of cross-disciplinary management and service innovation in the period of operations management, Cultural Ecosystem Service Innovation (CESI) framework is useful to support the practice and continuous improvement. A real-world case of Kaohsiung Dome in Taiwan has been benchmarked and analyzed with empirical data. With in-depth expert interviews, the paper demonstrates the use of CESI framework to support business strategy and operations management for sustainable system development and shared values. Management implications were addressed to promote multiple positive feedbacks with the government, enterprises, and the general public and jointly strive to support the development of a benchmarked city.
Keywords: 650; business model; cultural ecosystem; growth strategy; private finance initiative (PFI); public-private-partnership (PPP); service innovation; sustainable development